Best practices for hospital & health system pharmacy 2013-2014 : position and guidance documents of ASPH. - American Society of Health-System Pharmacists (Bethesda, MD : American Society of Health-System Pharmacists, 2013)
SHP position statements and more than 70 guidance documents of varying scope provide ongoing advice to managers and practitioners to help improve the medication-use process, patient care and safety, and patient outcomes and quality of life. New or revised material in this edition includes: Clinical Practice Guidelines for Antimicrobial Prophylaxis in Surgery Clinical Practice Guidelines for the Management of Pain, Agitation, and Delirium in Adult Patients in the Intensive Care Unit ASHP Therapeutic Position Statement on the Role of Pharmacotherapy in Preventing Venous Thromboembolism in Hospitalized ASHP Guidelines on Compounding Sterile Preparations ASHP Guidelines on Home Infusion Pharmacy Services ASHP Statement on the Pharmacy Technician s Role in Pharmacy Informatics ASHP Statement on the Pharmacist s Role in Substance Abuse Prevention, Education, and Assistance.
Keywords: Pharmacy -- standards; Pharmacists -- standards; Pharmacy Service, Hospital -- standards